Clinical Efficacy and Safety of Mesenchymal Stem Cells for Systemic Lupus Erythematosus - Tianbiao Zhou; Hong-Yan Li; Chunling Liao; Wenshan Lin; Shujun Lin (Hindawi Limited, 2020)
Systemic lupus erythematosus (SLE) is a polymorphic, multisystemic autoimmune disease that causes multiorgan damage in which cellular communication occurs through the involvement of autoantibodies directed against autoantigen production. Mesenchymal stem cells (MSCs), which have strong protective and immunomodulatory abilities, are obtained not only from bone marrow but also from medical waste such as adipose tissue and umbilical cord tissue and have been recognized as a promising tool for the treatment of various autoimmune diseases and inflammatory disorders. This meta-analysis is aimed at assessing whether MSCs can become a new treatment for SLE with good efficacy and safety. Based on predetermined criteria, a bibliographical search was performed from January 1, 2000, to July 31, 2019, by searching the following databases: ISI Web of Science, Embase, PubMed, the Cochrane Library, and the Chinese Biomedical Literature Database (CBM). Eligible studies and data were identified. Statistical analysis was conducted to assess the efficacy (proteinuria, systemic lupus erythematosus disease activity index (SLEDAI), Scr, BUN, albumin, C3, and C4) and safety (rate of adverse events) of MSCs for SLE using Cochrane Review Manager Version 5.3. Ten studies fulfilled the inclusion criteria and were eligible for this meta-analysis, which comprised 8 prospective or retrospective case series and four randomized controlled trails (RCTs) studies. In the RCT, the results indicated that the MSC group had lower proteinuria than the control group at 3 months and 6 months and the MSC group displayed a lower SLEDAI than the control group at 2 months and 6 months. Furthermore, the MSC group showed a lower rate of adverse events than the control group (OR=0.26, 95% CI: 0.07, 0.89, P=0.03). In the case series trials, the results indicated that the MSC group had lower proteinuria at 1 month, 2 months, 3 months, 4 months, 6 months, and 12 months. In conclusion, MSCs might be a promising therapeutic agent for patients with SLE.